Aplicação de extratos enzimáticos contendo lacases fúngicas para a biorremediação de fármacos - Gambato, Gabriela (My University, 2026)
The presence of emerging contaminants, especially pharmaceuticals, in the environment has become a global concern. Due to their persistence and low biodegradability, these substances present significant challenges to conventional treatment systems, resulting in their accumulation in ecosystems. In this context, laccases emerge as promising bioremediation tools because they catalyze reactions under mild conditions, with high efficiency and low environmental impact. Thus, this thesis aimed to analyze the potential of fungal laccases in the bioremediation of pharmaceuticals through two complementary approaches: (i) a scientometric study to map research trends, collaboration networks, and thematic gaps; and (ii) an experimental investigation focused on the production and application of crude extracts containing fungal laccases in the bioremediation of pharmaceuticals. The scientometric study revealed that research on laccases applied to the bioremediation of pharmaceuticals is expanding, mainly concentrated in Environmental Sciences, Environmental Engineering, and Microbiology Applied to Biotechnology. Cohesive research groups were identified, but with limited connectivity between clusters, reinforcing the need for greater internationalization and interdisciplinary cooperation. The journals Chemosphere, Bioresource Technology, and Environmental Science and Pollution Research stood out as central vehicles for the publication of studies. Keyword mapping showed a focus on immobilization, wastewater, and degradation, highlighting pharmaceuticals such as diclofenac, estrogens, tetracycline, and carbamazepine, while other compounds such as antitumor drugs and thyroid hormones remain underexplored. In the experimental stage, the species Agaricus blazei, Marasmiellus palmivorus VE111, Pycnoporus sanguineus 14G, and Trametes sp. 50/90 were cultivated, which were evaluated for mycelial development kinetics and biochemical parameters such as pH, carbohydrate and protein consumption, and laccase production. The enzymatic extracts obtained were subsequently evaluated for storage stability and bioremediation capacity of the pharmaceuticals acetaminophen and diclofenac. Distinct profiles of enzymatic production, biomass, and metabolism were observed for each culture. Stabilization with glycerol and lyophilization enabled the maintenance of laccase activity during the storage period. In bioremediation, M. palmivorus VE111 showed the highest percentage of acetaminophen degradation (96%), while A. blazei showed the highest degradation of diclofenac (82%). Taken together, the results indicate that fungal laccases constitute a promising, economical, and sustainable alternative for the bioremediation of drugs. The integration of scientometric and experimental findings provides support for scientific and technological advancement in the field, guiding future research, public policies, and the development of innovation strategies aimed at tackling environmental contamination by pharmaceuticals. [resumo fornecido pelo autor]
A presença de contaminantes emergentes, especialmente fármacos e produtos farmacêuticos, no meio ambiente tem se consolidado como uma preocupação global. Essas substâncias, devido à sua persistência e baixa biodegradabilidade, apresentam desafios significativos para os sistemas de tratamento convencionais, o que resulta em sua acumulação nos ecossistemas. Nesse contexto, as lacases emergem como ferramentas promissoras de biorremediação por catalisarem reações sob condições brandas, com alta eficiência e baixo impacto ambiental. Assim, esta tese teve como objetivo analisar o potencial das lacases fúngicas na biorremediação de fármacos por meio de duas abordagens complementares: (i) um estudo cienciométrico, para mapear tendências de pesquisa, redes de colaboração e lacunas temáticas; e (ii) uma investigação experimental, focada na produção e aplicação dos extratos brutos contendo lacases fúngicas na biorremediação de fármacos. O estudo cienciométrico revelou que a pesquisa sobre lacases aplicadas à biorremediação de fármacos encontra-se em expansão, concentrada principalmente em Ciências Ambientais, Engenharia Ambiental e Microbiologia Aplicada à Biotecnologia. Foram identificados grupos de pesquisa coesos, porém com conectividade limitada entre os clusters, reforçando a necessidade de maior internacionalização e cooperação interdisciplinar. Os periódicos Chemosphere, Bioresource Technology e Environmental Science and Pollution Research destacaram-se como veículos centrais de publicação dos estudos. O mapeamento de palavras-chave evidenciou foco em imobilização, águas residuais e degradação, com destaque para fármacos como diclofenaco, estrogênios, tetraciclina e carbamazepina, ao passo que outros compostos como antitumorais e hormônios tireoidianos permanecem pouco explorados. Na etapa experimental, foram cultivadas as espécies Agaricus blazei, Marasmiellus palmivorus VE111, Pycnoporus sanguineus 14G e Trametes sp. 50/90, as quais foram avaliadas quanto à cinética de desenvolvimento micelial e aos parâmetros bioquímicos, tais como pH, consumo de carboidratos, proteínas e produção de lacases. Os extratos enzimáticos obtidos foram posteriormente avaliados quanto à estabilidade de armazenamento e à capacidade de biorremediação dos fármacos paracetamol e diclofenaco. Foram observados perfis distintos de produção enzimática, biomassa e metabolismo para cada cultivo. A estabilização com o glicerol e a liofilização viabilizaram a manutenção da atividade das lacases no período de armazenamento. Na biorremediação, M. palmivorus VE111 apresentou o maior percentual de degradação do paracetamol (96%), enquanto o A. blazei para o diclofenaco (82%). Em conjunto, os resultados indicam que as lacases fúngicas constituem uma alternativa promissora, econômica e sustentável para a biorremediação de fármacos. A integração entre os achados cienciométricos e experimentais fornece subsídios para o avanço científico e tecnológico na área, orientando pesquisas futuras, políticas públicas e desenvolvimento de estratégias de inovação voltadas ao enfrentamento da contaminação ambiental por fármacos. [resumo fornecido pelo autor]
Keywords: Farmacologia - Biotecnologia - Aspectos ambientais; Biorremediação; Enzimas; Oxidases; Lacase; Fungos; Insumos farmacêuticos; Pharmacology - Biotechnology - Environmental aspects; Bioremediation; Enzymes; Laccase; Fungi; Pharmaceutical raw material